The Effect of Employment of Nursing Students on their Academic Achievement in the School of Nursing and Midwifery of Shahid Beheshti University of Medical Sciences - Beirami, Hajar; Rezghi Shirsavar, Hadi (Advances in Nursing & Midwifery, 2019)
Introduction: The present study was conducted to assess the effect of nursing students’ employment on their academic success in the School of Nursing and Midwifery of Medical Sciences University. Methods: In the present descriptive correlational study, the statistical population comprised all 1521 students of School of Nursing and Midwifery of ShahidBeheshti University of Medical Sciences in the academic year 2016-17. Sampling was performed by proportional stratified random method. Using Cochran equation, sample size was determined 309 students. Data were collected using demographic and academic success questionnaire and analyzed in SPSS-18. Results: The results showed that academic achievement has relationships with gender, marital status, and employment status of student, their spouse’semployment status and education, marital life, family housing, appropriate studying setting, and job relevance with academic discipline. According to logistic regression test, variables such as gender, marital status, spouse’s education and marital life were able to predict academic achievement. Conclusions: Personal and family status are highly effective on students’ academic achievement.